Libre comercio pactado con una superpotencia - Jorge C. Ávila (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2008)
– The purpose of the essay is to investigate the proposition that a free-trade treaty with a superpower is more effective in promoting exports, investment and per capita growth than a unilateral opening to free trade. To that end we study five success stories: Chile (unilateral opening), Mexico (treaty with a superpower), Spain (supranational integration), Japan (forced unilateral opening), and Argentina in the 19th century (informal treaty with a superpower). We conclude that the historical evidence supports the proposition. The wider the scope of the treaty and the stronger the partner, the greater the success.
Keywords: 330